KAJIAN HUKUM PERSAINGAN USAHA DI PELABUHAN MERAK - Sutisna, Deni; Ratnawati, Elfrida (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
The ferry port that connects Java Island and Sumatra Island with a distance of 15 miles and is the most populous ferry port in Indonesia is Merak Port. Ships that serve crossings from Java Island through Merak Port to Sumatra Island through Bakauheni Port Lampung are Ferry types that serve passenger and vehicle transportation. Merak Port is a commercial port, in the business process at Merak Port there is a dualism of business entity functions that manage the port while managing the ship. This research uses descriptive analysis, with the research approach used is a normative legal approach. This research focuses on applicable legal norms, both those contained in legislation and literature, especially business competition which will then be analyzed and deductively drawn conclusions. There is dualism in the function of a business entity at Merak Port, apart from being a Port business entity, it also doubles as a Ship Operator. This condition is very vulnerable to the emergence of unfair business competition, for this reason it is necessary to separate the functions between Port Operators and Ship Operators in order to create a conducive business climate, justice and legal certainty and each business entity can focus on the quality of service to consumers / service users.Keywords: Legal Studies, Business Competition, Ferry